2024
DOI: 10.1002/adfm.202402091
|View full text |Cite
|
Sign up to set email alerts
|

Tunable High‐Temperature Tunneling Magnetoresistance in All‐van der Waals Antiferromagnet/Semiconductor/Ferromagnet Junctions

Wen Jin,
Xinlu Li,
Gaojie Zhang
et al.

Abstract: Magnetic tunnel junctions (MTJs) are widely applied in spintronic devices for efficient spin detection through the imbalance of spin polarization at the Fermi level. The van der Waals (vdW) property of 2D magnets with atomically flat surfaces and negligible surface roughness greatly facilitates the development of MTJs, primarily in ferromagnets. Here, A‐type antiferromagnetism in 2D vdW single‐crystal (Fe0.8Co0.2)3GaTe2 is reported with TN ≈ 203 K in bulk and ≈ 185 K in 9‐nm nanosheets. The metallic nature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…However, this induction simultaneously alters the magnetic anisotropy of the obtained antiferromagnetic materials to the easy plane, rendering them unsuitable for vertically stacked heterostructures in MTJs. 16 The FGaT with large perpendicular magnetic anisotropy and high Tc is promising to address these challenges. Various methods, including electric-field, [17][18][19] strain, 20 doping, [21][22][23][24][25] and proximity effects, 26,27 have been employed to investigate RT 2D ferromagnets and antiferromagnets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this induction simultaneously alters the magnetic anisotropy of the obtained antiferromagnetic materials to the easy plane, rendering them unsuitable for vertically stacked heterostructures in MTJs. 16 The FGaT with large perpendicular magnetic anisotropy and high Tc is promising to address these challenges. Various methods, including electric-field, [17][18][19] strain, 20 doping, [21][22][23][24][25] and proximity effects, 26,27 have been employed to investigate RT 2D ferromagnets and antiferromagnets.…”
Section: Introductionmentioning
confidence: 99%
“…23 Similarly, A-type antiferromagnetism in (Fe 0.8 Co 0.2 ) 3 GaTe 2 has been observed, with T N values of approximately 203 K in bulk and 185 K in 9-nm-thick nanosheets during the submission of this paper. 16 Additionally, it has been reported that Ni with x = 0.03 substituting for Fe in (Fe 1− x Ni x ) 3 GaTe 2 crystals can enhance the coercive field ( H C ) up to ∼200% while maintaining the ferromagnetic state at room temperature. 28 Despite these findings, there are still very few studies on substitutional doping of FGaT, especially on tuning antiferromagnetism.…”
Section: Introductionmentioning
confidence: 99%